GROWTH OPPORTUNITY DAN RISIKO NILAI TUKAR TERHADAP PROFITABILITAS DENGAN FINANCIAL HEDGING SEBAGAI MODERASI - Suhartono , Jeffry; Lindrawati, Lindrawati ((JRAMB) Jurnal Riset Akuntansi Mercu Buana, 2024)
Profitability is very important for company sustainability. High profitability can be obtained from a high growth opportunity value. Companies that grow will expand and carry out international trade. Transactions between countries can cause losses due to unstable currency values. To reduce the impact of losses from unstable currency values, companies can hedge exchange rate risks using financial hedging. Many companies still feel that they do not need to use financial hedging. The aim of this research is to analyze the influence of growth opportunity and exchange rate risk on profitability with financial hedging as a moderating. The design of this research is quantitative research, with data in the form of annual reports and a summary of closing shares for the year. The research object is manufacturing companies listed on the IDX. The data analysis technique used is multiple linear regression and moderation. The research results show that growth opportunity has a positive effect on profitability, exchange rate risk does not have a significant effect on profitability, and financial hedging does not significantly moderate the effect of exchange rate risk on profitability. Even though financial hedging in this research is not proven, management still has to minimize the company's risk with financial hedging by looking at the research period which was conducted during the pandemic era, thus limiting for international transactions.